Congenital Unilesional Cutaneous Langerhans Cell Histiocytosis: A Case Report. (4th March 2021) - Ungari, Marco; Caresana, Gioachino; Tanzi, Giulia; Drera, Bruno; Frittoli, Marta Claudia; Gusolfino, Marino Daniel; Ferrero, Giuseppina; Varotti, Elena; Manotti, Laura; Trombatore, Monica; Bertoni, Ramona
Abstract: Langerhans cell histiocytosis (LCH) is a clonal proliferation of bone-marrow-derived cells, which normally reside as epidermal and mucosal dendritic cells involved in antigen presentation. It is a rare disease more common in children than adults, that is believed to be neoplastic in most cases. The diagnosis is based on clinical and radiological findings in combination with histopathologic, immunophenotypic, or ultrastructural analyses. LCH have a broad spectrum of clinical manifestations, ranging from benign cutaneous lesions to malignant multisystem disease. Based on the extent of involvement at diagnosis, LCH can be divided in single-system LCH when only one organ or system is involved, usually with multiple lesions, and multisystem LCH, when 2 or more organs or systems are involved at diagnosis. One variant of LCH is characterized by congenital isolated cutaneous involvement. It typically manifests at birth or in the postnatal period with a widespread eruption of red-to-brown papulo-nodules or, more uncommonly, a solitary lesion. The overall prognosis for single lesion skin limited LCH is excellent and most lesions spontaneously resolve within 4–18 weeks. Systemic involvement is rare. Skin findings cannot predict systemic disease and obtaining an oncology consultation is recommended for further evaluation. Herein, we present an additional case in a full-term, well-appearing, female infant with an isolated, asymptomatic, ulcerated, papule of the left arm, that was noted at birth.